An update on bone imaging and markers in chronic kidney disease. Issue 6 (1st November 2016) - Krishnasamy, Rathika; Hawley, Carmel M; Johnson, David W
ABSTRACT: Introduction: Bone disorders in chronic kidney disease (CKD) are associated with heightened risks of fractures, vascular calcification, poor quality of life and mortality compared to the general population. However, diagnosis and management of these disorders in CKD are complex and appreciably limited by current diagnostic modalities. Areas covered: Bone histomorphometry remains the gold standard for diagnosis but is not widely utilised and lacks feasibility as a monitoring tool. In practice, non-invasive imaging and biochemical markers are preferred to guide therapeutic decisions. Expert c ommentary: This review aims to summarize the risk factors for, and spectrum of bone disease in CKD, as well as appraise the clinical utility of dual energy X-ray densitometry, peripheral quantitative computed tomography, high-resolution peripheral quantitative computed tomography, and bone turnover markers.